1982
DOI: 10.1039/dt9820002099
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of the cluster dianion [Os10C(CO)24]2? by pyrolysis. X-Ray structure analysis of [N(PPh3)2]2[Os10C(CO)24] and [Os5C(CO)14H(NC5H4)]

Abstract: The Synthesis of the Cluster Dianion [Os, oC(CO)24]2-by Pyrolysis. X-Ray Structure Analysis of [ N(PPh3)2]2[O~10C(C0)24] t and [ oS&(co)~ 4H( N C d b ) ] *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 5 publications
0
32
0
Order By: Relevance
“…Thick-walled 35-mL reaction vessels with Teflon-lined caps were provided by CEM. Caution must be exercised due to the toxic nature of CO and Mo(CO) 6 . All manipulations must be carried out in a highly efficient fume hood.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thick-walled 35-mL reaction vessels with Teflon-lined caps were provided by CEM. Caution must be exercised due to the toxic nature of CO and Mo(CO) 6 . All manipulations must be carried out in a highly efficient fume hood.…”
Section: Methodsmentioning
confidence: 99%
“…Our initial target was the decanuclear osmium cluster [N(PPh 3 ) 2 ] 2 [Os 10 C(CO) 24 ]. The standard method for its synthesis involves pyrolysis for 64 h [6]. We have found that microwave irradiation can be used to make this cluster in just over 1 h.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations